2005
DOI: 10.1124/mol.105.015982
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Models of GABAA Receptor Extracellular and Transmembrane Domains: Important Insights in Pharmacology and Function

Abstract: Comparative models of the extracellular and transmembrane domains of GABA A receptors in the agonist-free state were generated based on the recently published structures of the nicotinic acetylcholine receptor. The models were validated by computational methods, and their reliability was estimated by analyzing conserved and variable elements of the cys-loop receptor topology. In addition, the methodological limits in the interpretation of such anion channel receptor models are discussed. Alignment ambiguities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
128
1
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(137 citation statements)
references
References 40 publications
7
128
1
1
Order By: Relevance
“…1, 6). Thus, despite the cogent rationale offered recently for a two residue gap in the M2-M3 loop (Ernst et al, 2005), it is not supported by our current experiments. Furthermore, our results imply that the relative depths of the M2 and M3 segments in the 2BG9 AChR structure are correct (Unwin, 2005).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…1, 6). Thus, despite the cogent rationale offered recently for a two residue gap in the M2-M3 loop (Ernst et al, 2005), it is not supported by our current experiments. Furthermore, our results imply that the relative depths of the M2 and M3 segments in the 2BG9 AChR structure are correct (Unwin, 2005).…”
Section: Discussioncontrasting
confidence: 99%
“…Recently, GABA A receptor homology models (Cromer et al, 2002;Trudell and Bertaccini, 2004;Ernst et al, 2005) were constructed based on the acetylcholine binding protein and Torpedo ACh receptor structures (Brejc et al, 2001;Miyazawa et al, 2003;Celie et al, 2004;Unwin, 2005). Homology models depend on the correct alignment of subunit sequences from different superfamily members.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although allosteric effects by the mutations cannot be fully excluded, we consider this possibility unlikely. Both AARs are predicted to be located in cytoplasmic leaflet of the M4 α-helix, in an angle of approximately 60°and a distance in the direction of the α-helix of 4.5 Å. Intriguingly, in a homology model described by Ernst et al (28), all four mentioned residues face the same cavity in the receptor.…”
Section: Resultsmentioning
confidence: 98%
“…However, a modelling study (Ernst et al, 2005) indicated the presence of multiple solvent accessible pockets within the GABAA receptor that could function as possible drug binding sites. Simultaneous drug interaction with several of these binding sites can explain the extremely complex pharmacology of these receptors.…”
Section: Introductionmentioning
confidence: 99%